Estudio de la calidad de las viviendas y las políticas públicas en el proyecto de interés social “la estancia el roble” en la ciudad de Tunja (2019)
The need to formulate public policies aimed at improving the quality of life of the population is an inherent issue in the use of appropriate measures in terms of technical quality and compliance with the expectations of the target population. The social interest housing project "Estancia el Roble" is a model for the implementation of public housing policy, which presents a series of deficiencies of a technical nature, social responsibility and political control, which generates effects that put at risk the quality of the work and the expectations of the users. Therefore, the objective of this article was to carry out an analysis from the technical, social and political perspective, in order to evaluate whether the public policies implemented in the area of social interest housing are efficient in the social interest housing projects. Among the results obtained, it was found that coordination, planning, execution, follow-up and evaluation, within a logical and technical framework, are not fully complied with, which generates shortcomings in construction projects. Likewise, it is evident that the implementation of public policy lacks follow-up and evaluation, which creates inconveniences, presenting partial compliance. Based on the results, it was possible to conclude that the inclusion of correct and responsible engineering elements allows public policies to be more comprehensive and to provide support when projecting and guaranteeing their execution. This research was carried out during the development of the subjects of the Specialization in Construction Project Management program at the Universidad Santo Tomás.